Effect of Teenage pregenancyon family stability in Bulisa Sub-County, Rubanda District - Noreen Akatukunda (Uganda Christian University, 2025)
The study assessed the impact of teenage pregnancy on family stability in Bubaare Sub-County, Rubanda District. The objectives of the study were; to investigate the causes of teenage pregnancy among teenagers in Bubaare Sub-County, to assess the effects of teenage pregnancy on family stability in Bubaare Sub-County and to identify coping strategies families use to deal with the challenges posed by teenage pregnancy in Bubaare Sub-County. A qualitative research approach was used and data was collected using interviews and questionnaires. The study findings on causes of teenage pregnancy among teenagers in Bubaare Sub-County were; peer pressure contributes to teenage pregnancy, lack of sex education leads to teenage pregnancy, poverty drives many teens into early sexual activity. The study findings on effects of teenage pregnancy on family stability in Bubaare Sub-County were; teenage pregnancy increases economic burden on families, teenage pregnancy leads to school dropout. The study findings on coping strategies families use to deal with the challenges posed by teenage pregnancy in Bubaare Sub-County were; families seek counseling services to handle teenage pregnancies. It was suggested in this research that policymakers create and introduce comprehensive sexuality education policies that are culturally sensitive as well as age-appropriate to manage the core causes of adolescent pregnancy. In summary, research unveiled that adolescent pregnancy impacts family stability in Rubanda District's Bubaare Sub-County considerably through added economic pressures, emotional distress, school dropouts, inter-family disagreements, and damage to reputation. The research identified significant contributing factors as peer pressure, poverty, absence of sexual education, fragmented households, as well as media influence. Families counter these through seeking counseling, enlisting religious leaders' involvement, aid from extended family members, education priority on the adolescent mother's part, as well as in a few instances through early marriage